Dual band dual polarized antenna with high efficiency for base transceiver stations - Kashani, F.H.; Shahpari, M.; Ameri Mahabadi, H. (2008)
In this paper new array element for use in dual band dual polarized antenna will be introduced that has high efficiency (more than 95) and has high isolation in both 900MHz and 1800MHz bands. Also radiation pattern of this antenna is according to IEC recommendation.